2018
DOI: 10.1002/adsc.201800642
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of Vicinal Sulfur‐containing Tetrasubstituted Stereocenters via Organocatalyzed Mannich‐Type Addition of Rhodanines to Isatin Imines

Abstract: The catalyzed enantioselective nucleophilic addition of rhodanines has been established by employing isatin-derived imines as suitable partners under chiral squaramide catalysis. By using this strategy, the resulting 3-substituted 3-amino-2oxindoles featuring both rhodanine and vicinal sulfur-containing tetrasubstituted stereocenters structural motifs were obtained in high yields with excellent enantioselectivities and diastereoselectivities.Skeletons with sulfur-containing tetrasubstituted carbon stereocenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The investigation of the azodicarboxylate partner indicated that the ester moiety has a profound effect on the asymmetric induction. Very recently, we have established a chiral squaramide mediated Mannich‐type additions of rhodanines to isatin imines, which enables the formation of a variety of 3‐substituted 3‐amino‐2‐oxindoles featuring both rhodanine and vicinal sulfur‐containing tetrasubstituted stereocenters structural motifs in generally high yields with excellent stereoselectivities (Scheme E) . Despite these elegant works, the organocatalytic asymmetric nucleophilic additions of rhodanines for assembling of sulfur‐containing tetrasubstituted carbon stereocenter are still far from well‐developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of the azodicarboxylate partner indicated that the ester moiety has a profound effect on the asymmetric induction. Very recently, we have established a chiral squaramide mediated Mannich‐type additions of rhodanines to isatin imines, which enables the formation of a variety of 3‐substituted 3‐amino‐2‐oxindoles featuring both rhodanine and vicinal sulfur‐containing tetrasubstituted stereocenters structural motifs in generally high yields with excellent stereoselectivities (Scheme E) . Despite these elegant works, the organocatalytic asymmetric nucleophilic additions of rhodanines for assembling of sulfur‐containing tetrasubstituted carbon stereocenter are still far from well‐developed.…”
Section: Methodsmentioning
confidence: 99%
“…to afford the 1,4‐adducts in high yields with good to high stereoselectivities. Based on our previous work on azadienes, and as a part of our ongoing interest in the catalytic enantioselective construction of sulfur‐containing carbon stereocenters,, herein we report an organocatalytic asymmetric Michael addition of rhodanines to 2‐arylidene‐ N ‐tosylbenzofuran‐3(2 H )‐imines, affording benzofurans bearing both rhodanine and sulfur‐containing tetrasubstituted stereocenter structural motif in good to high yields with good to excellent enantio‐ and diastereoselectivities (Scheme E).…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Li group [37] attempted to perform an enantioselective Mannich reaction of rhodanines 29 to isatin‐derived ketimines 23 catalyzed by bifunctional squaramide catalyst C3 (Scheme 12). Surprisingly, the desired Mannich products 30 containing chiral 3‐substituted‐3‐amino‐2‐oxindole scaffolds and rhodanines were smoothly obtained.…”
Section: Asymmetric Mannich Reactions Using Isatin‐derived Ketiminesmentioning
confidence: 99%
“…In consideration of structurally related to thiazolones and based on our success in organocatalytic Mannichtype reaction of thiazolones with isatin imines, we then investigated the Mannich-type addition of rhodanines 101 to isatin imines 102 (Scheme 29). [37] In the presence of quinine-based squaramide C35 with a loading of 1 mol%, diversified optically active 3- Under the same content, Wu et al employed a tertiary amine-thiourea C36 as catalyst to complete the asymmetric Mannich-type reaction between rhodanines 104 and isatin imines 105 (Scheme 30). [38] The reaction was carried out at À 30°C and the desired products 106 were obtained in 43-99% yields with 36-97% ee and 98:2-99:1 dr.…”
Section: Mannich-type Reactionmentioning
confidence: 99%